Electrode for solid-state battery, and solid-state battery
By introducing a reaction between a specific metal and a sulfide solid electrolyte in a solid battery, the problem of increasing resistance of the solid battery is solved, and the performance and stability of the battery are improved.
Patent Information
- Application Number
- CN202410660188.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2024-05-27
- Publication Date
- 2024-12-31
AI Technical Summary
The resistance of solid batteries increases during repeated charging and discharging, resulting in battery deterioration, and the prior art is difficult to effectively suppress this problem.
A specific content of metals, such as copper, silver, etc., is introduced into the positive electrode layer or negative electrode layer of a solid battery. By reacting with a sulfide solid electrolyte, metal sulfide or phosphorothioate is formed to improve electron and ion conductivity and reduce the Resistance increases.
By introducing specific metals, the reaction between the sulfide solid electrolyte and the metal effectively suppresses the increase in resistance, improves the performance of the solid battery, and reduces the deterioration speed of the battery.
Smart Images

Figure CN119230723A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrode for a solid battery and a solid battery. Background Art
[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras and mobile phones, the development of batteries used as their power sources has attracted attention. Among them, lithium-ion batteries have attracted much attention due to their high energy density and excellent safety.
[0003] In the past, in batteries used for such purposes, since an electrolyte containing a flammable organic solvent was used, it was necessary to install a safety device to suppress the temperature rise during a short circuit, and to improve the structure and materials used to prevent short circuits. In contrast, by replacing the electrolyte with a solid electrolyte, the battery is solidified, and no flammable organic solvent is used in the battery, which can simplify the safety device and improve the manufacturing cost and productivity. Therefore, the development of batteries in which the electrolyte is replaced with a solid electrolyte layer is underway.
[0004] Generally, when a positive electrode layer and a negative electrode layer included in a solid battery contain metal such as copper, they are removed because they may cause a short circuit.
[0005] For example, in Patent Document 1, a solid battery including a positive electrode layer, a sulfide solid electrolyte layer, and a negative electrode layer is aged before initial charge, whereby metals such as copper are melted and removed.
[0006] Prior art literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-191183 Summary of the invention
[0008] Solid-state batteries tend to have increased resistance due to repeated charge and discharge. Increased resistance means that battery degradation due to charge and discharge of the battery increases.
[0009] Here, the present inventors have found that the increase in the resistance can be suppressed by containing a specific metal at a specific content ratio in the positive electrode layer or the negative electrode layer.
[0010] One embodiment of the present disclosure has been made in view of the above circumstances, and an object of the present disclosure is to provide a solid battery electrode and a solid battery capable of reducing an increase in resistance of a solid battery.
[0011] Means for solving the above-mentioned problems include the following embodiments.
[0012] <1>
[0013] A battery for a solid battery, comprising:
[0014] Sulfide solid electrolytes, and
[0015] a metal that reacts with the sulfide solid electrolyte to exhibit electronic conductivity,
[0016] The content of the metal relative to the total volume of the solid battery electrode is 5 volume ppm or more and less than 10,000 volume ppm.
[0017] <2>
[0018] According to the above <1> The solid battery electrode described herein is characterized in that the metal is at least one metal selected from the group consisting of copper, silver, nickel, iron, tin, aluminum, titanium, chromium, zinc, gold, magnesium, antimony, zirconium, molybdenum and alloys thereof.
[0019] <3>
[0020] According to the above <2> In the solid battery electrode described herein, the metal is at least one of copper and silver.
[0021] <4>
[0022] According to the above <1> ~ <3> The solid battery electrode according to any one of the above, wherein the content of the metal relative to the total volume of the solid battery electrode is 50 volume ppm or more.
[0023] <5>
[0024] According to the above <1> ~ <4> The solid battery electrode according to any one of the above, wherein the content of the metal relative to the total volume of the solid battery electrode is 5,000 volume ppm or less.
[0025] <6>
[0026] according to <1> ~ <5> The solid battery electrode according to any one of claims , wherein the sulfide solid electrolyte contains phosphorus atoms.
[0027] <7>
[0028] A solid battery comprises a positive electrode layer, a solid electrolyte layer and a negative electrode layer.
[0029] At least one of the positive electrode layer and the negative electrode layer is <1> ~ <6> The solid battery electrode according to any one of the above.
[0030] According to one embodiment of the present disclosure, a solid battery electrode and a solid battery capable of reducing an increase in resistance of a solid battery can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic cross-sectional view showing one embodiment of the solid electrolyte disclosed in the present invention.
[0032] Description of Reference Numerals
[0033] A: negative electrode layer, B: solid electrolyte layer, C: positive electrode layer, 101: negative electrode active material, 103: positive electrode active material, 105 and 107: conductive additive, 109 and 111: binder, 113: negative electrode collector, 115: positive electrode collector DETAILED DESCRIPTION
[0034] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the minimum value and the maximum value, respectively.
[0035] In the numerical ranges recorded in stages in the present disclosure, the upper limit or lower limit recorded in a certain numerical range may also be replaced by the upper limit or lower limit of another numerical range recorded in stages. In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in a certain numerical range may also be replaced by the value shown in the embodiments.
[0036] In the present disclosure, a combination of two or more preferred aspects is a more preferred aspect.
[0037] In the present disclosure, when there are a plurality of substances corresponding to each component, the amount of each component means the total amount of the plurality of substances unless otherwise specified.
[0038] In the present disclosure, "solid electrolyte" refers to an electrolyte that remains solid at 25°C under a nitrogen atmosphere.
[0039] In the present disclosure, “sulfide solid electrolyte” includes both a crystalline sulfide solid electrolyte having a crystal structure and an amorphous sulfide solid electrolyte.
[0040] In the present disclosure, a crystalline sulfide solid electrolyte refers to a solid electrolyte in which a peak derived from a solid electrolyte is observed in an X-ray diffraction pattern in a powder X-ray diffraction (XRD) measurement, and is a material that is independent of the presence or absence of a peak derived from a raw material of the solid electrolyte. That is, the crystalline sulfide solid electrolyte contains a crystal structure derived from the solid electrolyte, and may be a crystal structure derived from the solid electrolyte in part or in whole. Furthermore, if the crystalline sulfide solid electrolyte has an X-ray diffraction pattern as described above, an amorphous sulfide solid electrolyte (also referred to as a "glass component") may be contained in part. Therefore, the crystalline sulfide solid electrolyte includes so-called glass ceramics obtained by heating an amorphous solid electrolyte (glass component) to a crystallization temperature or higher.
[0041] In addition, in the present disclosure, an amorphous sulfide solid electrolyte (glass component) refers to an X-ray diffraction pattern in a powder X-ray diffraction (XRD) measurement in which substantially no peaks other than peaks derived from the material are observed, and is a pattern that is unrelated to the presence or absence of peaks derived from the raw materials of the solid electrolyte.
[0042] [Solid battery electrodes]
[0043] The solid battery electrode disclosed in the present invention contains a sulfide solid electrolyte and a metal (hereinafter also referred to as "specific metal") that reacts with the sulfide solid electrolyte to exhibit electron conductivity.
[0044] The content of the metal relative to the total volume of the solid battery electrode is 5 volume ppm or more and less than 10,000 volume ppm.
[0045] According to the solid battery electrode disclosed in the present invention, the resistance increase of the solid battery can be reduced. The reason why the above effect is achieved is not entirely clear, but it is presumed as follows.
[0046] The solid battery electrode disclosed in the present invention contains a sulfide solid electrolyte and a specific metal of 5 volume ppm or more. When heat is generated during charge and discharge, the sulfide solid electrolyte and the specific metal react to produce a sulfide metal or a thiophosphate metal. It is speculated that due to their excellent electronic conductivity, the efficiency of the electronic conduction path is improved and the increase in resistance is suppressed. In addition, it is speculated that the reaction between the sulfide solid electrolyte and the specific metal imparts electronic conductivity to the sulfide solid electrolyte, and the increase in resistance is suppressed.
[0047] Furthermore, it is estimated that by setting the content of the specific metal in the solid battery electrode of the present disclosure to less than 10,000 ppm by volume, a decrease in ion conductivity can be suppressed, thereby suppressing an increase in resistance.
[0048] Furthermore, as shown in the examples described later, the reduction of the resistance increase of the solid battery can also be evaluated by the resistance of the solid battery after the heat treatment.
[0049] (Sulfide solid electrolyte)
[0050] The sulfide solid electrolyte may contain lithium atoms, sulfur atoms, and halogen atoms.
[0051] From the viewpoint of further suppressing the increase in resistance by reacting the sulfide solid electrolyte with the specific metal, the sulfide solid electrolyte preferably contains phosphorus atoms. When the sulfide solid electrolyte contains phosphorus atoms, a thiophosphate metal is generated, and both ion conductivity and electron conductivity can be achieved.
[0052] Sulfide solid electrolytes can be either amorphous or crystalline.
[0053] In one embodiment, the composition of the sulfide solid electrolyte is represented, for example, by xLi2S·(100-x)P2S5 (70≤x≤80), yLiI·zLiBr·(100-y-z)(xLi2S·(1-x)P2S5) (0.7≤x≤0.8, 0≤y≤30, 0≤z≤30), etc.
[0054] In addition, the sulfide solid electrolyte may also have a composition represented by the following general formula (1).
[0055] Li 4-x Ge 1-x P x S4 (0<x<1) Formula (1)
[0056] In formula (1), at least a part of Ge may be substituted by at least one selected from Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. In addition, at least a part of P may be substituted by at least one selected from Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. A part of Li may be substituted by at least one selected from Na, K, Mg, Ca, and Zn. A part of S may be substituted by a halogen. As the halogen, it is at least one of F, Cl, Br, and I.
[0057] Examples of the amorphous sulfide solid electrolyte include solid electrolytes composed of lithium sulfide, phosphorus sulfide, and lithium halide such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc.; and solid electrolytes such as Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI, etc. that contain other atoms such as oxygen atoms and silicon atoms.
[0058] From the viewpoint of obtaining higher ionic conductivity, it is preferably selected solid electrolytes composed of lithium sulfide, phosphorus sulfide, and lithium halide such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc.
[0059] The types of atoms constituting the amorphous sulfide solid electrolyte can be confirmed, for example, by an ICP emission spectroscopic analysis device.
[0060] The crystalline sulfide solid electrolyte may also be a so-called glass ceramic obtained by heating the amorphous solid electrolyte to a temperature above the crystallization temperature. As its crystal structure, there can be cited a Li3PS4 crystal structure, a Li4P2S6 crystal structure, a Li7PS6 crystal structure, a Li7P3S 11Crystal structure, a crystal structure having peaks near 2θ=20.2° and 23.6° (for example, Japanese Patent Application Laid-Open No. 2013-16423), etc. In addition, Li 4-x Ge 1-x P x The S4 series sulfide-LISICON domain II crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148 (7) A742-746 (2001)) is similar to Li 4-x Ge 1-x P x S4 is a crystal structure similar to the thio-LISICON Region II type (see Solid State Ionics, 177 (2006), 2721-2725)).
[0061] The shape of the sulfide solid electrolyte is not particularly limited, and may be, for example, a granular shape. The average particle size (D 50 ) For example, the range of 0.01 μm to 500 μm and 0.1 to 200 μm can be exemplified.
[0062] The content of the sulfide solid electrolyte relative to the total mass of the solid battery electrode is preferably 2% by mass to 90% by mass, and more preferably 5% by mass to 30% by mass.
[0063] The content (volume ratio) of the sulfide solid electrolyte relative to the total volume of the solid battery electrode is preferably 3% by volume to 95% by volume, and more preferably 4% by volume to 85% by volume.
[0064] (Specified Metals)
[0065] The solid battery electrode disclosed herein contains a metal (specific metal) that reacts with a sulfide solid electrolyte to exhibit electronic conductivity. As the specific metal, for example, at least one metal selected from copper, silver, nickel, iron, tin, aluminum, titanium, chromium, zinc, gold, magnesium, antimony, zirconium, molybdenum and alloys thereof can be cited. Among the above, from the viewpoint of further reducing the increase in resistance, at least one of copper and silver is preferred, and copper is more preferred.
[0066] The shape of the metal is not particularly limited, and may be granular or non-granular.
[0067] Here, a method for verifying whether a metal is a metal (specific metal) that reacts with a sulfide solid electrolyte to exhibit electronic conductivity is described. First, the metal to be verified and the sulfide solid electrolyte are mixed and heat treated to obtain a sample. At this time, the mixing conditions and heat treatment conditions are set as follows.
[0068] Mixing conditions: The sulfide solid electrolyte and the target metal (using metal powder) were mixed so that the volume concentration of the metal powder was 5%. 1 g of the sulfide solid electrolyte and the metal powder with a volume concentration of 5% were weighed and thoroughly dry-mixed in a mortar for 5 minutes to obtain a mixed powder.
[0069] Heat treatment conditions: The Swagelok cell shown below was placed in a thermostatic bath set at 150° C. and heat treated for 7 days. After 7 days, it was taken out of the thermostatic bath, cooled to 25° C., and the electronic conductivity after heat treatment was measured.
[0070] Next, the electron conductivity of the obtained samples before and after the heat treatment was measured by the following method.
[0071] Weigh 200 mg of the sample and place it in a cylinder made by Swagelok. 2 The pellets are clamped with SUS pins at both ends and tightened with bolts to apply restraining pressure to the pellets. The battery in which pellets are sealed in a cylinder manufactured by Swagelok is called a Swagelok battery. For the heat-treated sample, the Swagelok battery is subjected to heat treatment under the heat treatment conditions. The obtained sample is kept at 25°C, and the electronic conductivity is calculated by a DC polarization method. The measurement was performed using an electrochemical workstation Celltest and an impedance analyzer Solartron 1260 manufactured by Solartron. The voltage was applied for 30 seconds at 0.1V, 0.2V, and 0.3V, and the current was measured. The resistance is calculated based on the relationship between the applied voltage and the current, and the electronic conductivity is calculated.
[0072] Then, the electronic conductivity before and after the heat treatment is compared. The increase rate of the electronic conductivity is calculated by dividing the electronic conductivity after the heat treatment by the electronic conductivity before the heat treatment. If the increase rate of the electronic conductivity is 2.17 or more, it is judged to be a metal (specific metal) that reacts with the sulfide solid electrolyte to exhibit electronic conductivity.
[0073] When the specific metal is in a particulate form, the smaller the particle size, the higher the reactivity with the sulfide solid electrolyte, and the greater the effect can be exhibited, which is preferred.
[0074] From the viewpoint of reacting the sulfide solid electrolyte and the specific metal to further reduce the increase in resistance, the content of the specific metal relative to the total volume of the solid battery electrode is preferably 20 volume ppm or more, more preferably 100 volume ppm or more, further preferably 200 volume ppm or more, particularly preferably 450 volume ppm or more, most preferably 600 volume ppm or more, and may be 1000 volume ppm or more.
[0075] From the viewpoint of suppressing the decrease in ionic conductivity and further reducing the increase in resistance, the content of the specific metal relative to the total volume of the solid battery electrode is preferably 8000 volume ppm or less, more preferably 7000 volume ppm or less, further preferably 6000 volume ppm or less, particularly preferably 5500 volume ppm or less, and may also be 5000 volume ppm or less.
[0076] Furthermore, from the viewpoint of reducing the self-discharge amount and suppressing short circuit, the content of the specific metal relative to the total volume of the solid battery electrode is more preferably 4000 volume ppm or less, and even more preferably 3000 volume ppm or less.
[0077] In the present disclosure, the content rate (volume ratio) of a specific metal in a solid battery electrode can be measured by the following method.
[0078] The cross section of the solid battery electrode is observed with a scanning electron microscope equipped with EDS (SEM-EDS, magnification 30,000 times), and elemental analysis is performed using energy dispersive spectroscopy (EDS), thereby enabling the content (volume ratio) of a specific metal to be measured.
[0079] (Active substance)
[0080] The solid battery electrode disclosed in the present invention may contain an active material. The active material may be a positive electrode active material or a negative electrode active material.
[0081] As the positive electrode active material, it is preferred to contain a lithium composite oxide. The lithium composite oxide may also contain at least one selected from F, Cl, N, S, Br and I. In addition, the lithium composite oxide may also have a crystal structure belonging to at least one space group selected from space groups R-3m, Immm and P63-mmc (also referred to as P63mc, P6 / mmc). In addition, the main arrangement of transition metals, oxygen and lithium in the lithium composite oxide may also be an O2 type structure.
[0082] Examples of lithium composite oxides having a crystal structure belonging to R-3m include Li x Me y O α X βA compound represented by (Me represents at least one selected from Mn, Co, Ni, Fe, Al, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, and P; X represents at least one selected from F, Cl, N, S, Br, and I; 0.5 ≤ x ≤ 1.5, 0.5 ≤ y ≤ 1.0, 1 ≤ α < 2, 0 < β ≤ 1).
[0083] As the lithium composite oxide having a crystal structure belonging to Immm, for example, a composite oxide represented by Li x1 M 1 A 1 2 (satisfying 1.5 ≤ x1 ≤ 2.3, M 1 contains at least one selected from Ni, Co, Mn, Cu, and Fe, A 1 contains at least oxygen, and the ratio of oxygen in A 1 is 85 atomic% or more) (a specific example is Li2NiO2), a composite oxide represented by Li x1 M 1A 1-x2 M 1B x2 O 2-y A 2 y (0 ≤ x2 ≤ 0.5, 0 ≤ y ≤ 0.3, at least one of x2 and y is not 0, M 1A represents at least one selected from Ni, Co, Mn, Cu, and Fe, M 1B represents at least one selected from Al, Mg, Sc, Ti, Cr, V, Zn, Ga, Zr, Mo, Nb, Ta, and W, and A2 represents at least one selected from F, Cl, Br, S, and P).
[0084] As the lithium composite oxide having a crystal structure belonging to P63 - mmc, for example, a composite oxide represented by M1 x M2 y O2 (M1 represents an alkali metal (preferably at least one of Na and K), M2 represents a transition metal (preferably at least one selected from Mn, Ni, Co, and Fe), and x + y satisfies 0 < x + y ≤ 2).
[0085] As the lithium composite oxide having an O2 - type structure, for example, a composite oxide represented by Li x [Li α (Mn a Co b M c ) 1-αA composite oxide represented by O2 (0.5 < x < 1.1, 0.1 < α < 0.33, 0.17 < a < 0.93, 0.03 < b < 0.50, 0.04 < c < 0.33, where M represents at least one selected from Ni, Mg, Ti, Fe, Sn, Zr, Nb, Mo, W, and Bi). As a specific example, Li can be cited. 0.744 [Li 0.145 Mn 0.625 Co 0.115 Ni 0.115 O2 etc.
[0086] As the negative electrode active material, silicon, silicon alloy, silicon oxide, etc. can be cited. In addition, as the negative electrode active material, metallic lithium, metallic indium, metallic aluminum, metallic silicon, metallic tin, etc., metallic lithium or a metal capable of forming an alloy with metallic lithium, oxides of these metals, alloys of these metals and metallic lithium, etc. can also be used. As the oxide, for example, Li4Ti5O 12 etc. oxide active materials can be cited. In addition, carbon etc. can also be cited as the negative electrode active material. As the carbon, natural graphite, artificial graphite, or hard carbon (difficult graphitization carbon) or soft carbon (easy graphitization carbon) can be cited. As the artificial graphite, highly oriented graphite, mesocarbon microbeads, etc. can be cited.
[0087] The content rate of the active material of each of the positive electrode and the negative electrode in the electrode for a solid battery of the present disclosure is preferably 20% by mass to 99% by mass, more preferably 50% by mass to 90% by mass, relative to the total mass of the positive electrode or the total mass of the negative electrode. However, regarding the negative electrode, when Li metal etc. is used, the content rate of the active material can also be 100% by mass.
[0088] In addition, the content rate (volume ratio) of the active material of each of the positive electrode and the negative electrode is preferably 10% by volume to 99% by volume, more preferably 32% by volume to 81% by volume, relative to the total volume of the positive electrode or the total volume of the negative electrode.
[0089] (Conductive aid)
[0090] The electrode for a solid battery of the present disclosure may contain a conductive aid.
[0091] As the conductive aid, carbon-based materials such as artificial graphite, graphite carbon fiber, resin-fired carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads, furfuryl resin-fired carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and difficult graphitization carbon can be cited.
[0092] The content rate of the conductive aid of each of the positive electrode and the negative electrode in the electrode for a solid battery of the present disclosure is preferably 0% by mass to 20% by mass, more preferably 0% by mass to 3% by mass, relative to the total mass of the positive electrode or the total mass of the negative electrode.
[0093] The content (volume ratio) of the conductive additive in each of the positive electrode and the negative electrode is preferably 0% to 45% by volume, more preferably 0% to 5.5% by volume, relative to the total volume of the positive electrode or the total volume of the negative electrode.
[0094] (Adhesive)
[0095] The solid battery electrode of the present disclosure may contain a binder.
[0096] Examples of the binder include various resins such as fluorine-based polymers such as polytetrafluoroethylene and polyvinylidene fluoride, thermoplastic elastomers such as butyl rubber and styrene-butadiene rubber, acrylic resins, acrylic polyol resins, polyvinyl acetal resins, polyvinyl butyral resins, and silicone resins.
[0097] The content of the binder in each of the positive electrode and the negative electrode of the solid battery electrode disclosed herein is preferably 0 to 10% by mass, more preferably 0 to 3% by mass, relative to the total mass of the positive electrode or the total mass of the negative electrode.
[0098] The content (volume ratio) of the binder in each of the positive electrode and the negative electrode is preferably 0% to 42.5% by volume, more preferably 0% to 12% by volume, relative to the total volume of the positive electrode or the total volume of the negative electrode.
[0099] (Other ingredients)
[0100] The solid battery electrode disclosed in the present invention may also contain components other than the above components (hereinafter also referred to as "other components"). Examples of other components include solid electrolytes other than sulfide solid electrolytes. Examples of solid electrolytes other than sulfide solid electrolytes include oxide solid electrolytes, halogenated solid electrolytes, and the like.
[0101] As an oxide solid electrolyte, it is preferred to contain oxygen (O) as the main component of the anion element, and for example, it may contain Li, Q element (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W and S) and O. As oxide solid electrolytes, garnet-type solid electrolytes, perovskite-type solid electrolytes, NASICON-type solid electrolytes, Li-PO-based solid electrolytes, Li-BO-based solid electrolytes, etc. can be cited. As garnet-type solid electrolytes, for example, Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x ) 12 (0≤x≤2), Li5La3Nb2O 12etc. As perovskite-type solid electrolytes, examples include (Li, La)TiO3, (Li, La)NbO3, (Li, Sr)(Ta, Zr)O3, etc. As NASICON-type solid electrolytes, examples include Li(Al, Ti)(PO4)3, Li(Al, Ga)(PO4)3, etc. As Li-P-O-based solid electrolytes, Li3PO4, LIPON (a compound in which a part of Li3PO4O is replaced by N) can be cited. As Li-B-O-based solid electrolytes, Li3BO3, a compound in which a part of the O in Li3BO3 is replaced by C, etc. can be cited.
[0102] As a halide solid electrolyte, a solid electrolyte containing Li, M, and X is preferred (M represents at least one of Ti, Al, and Y, and X represents F, Cl, or Br). Specifically, Li 6-3z Y z X6 (X represents Cl or Br, and z satisfies 0 < z < 2), Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≤ 1.5). In Li 6-3z Y z X6, from the perspective of excellent lithium ion conductivity, Li3YX6 (X represents Cl or Br) is more preferred, and Li3YCl6 is further preferred. Additionally, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≤ 1.5) is, for example, preferably contained together with a solid electrolyte such as a sulfide solid electrolyte from the viewpoints of suppressing oxidative decomposition of the sulfide solid electrolyte, etc., and more preferably covers at least a part of the surface of a solid electrolyte such as a sulfide solid electrolyte. Thereby, the lithium ion conductivity becomes better.
[0103] (Use)
[0104] The electrode for a solid battery of the present disclosure is suitable as a material for constituting the positive electrode or the negative electrode of a solid battery.
[0105] [Solid battery]
[0106] The solid battery of the present disclosure includes a positive electrode layer, a solid electrolyte layer, and a negative electrode layer,
[0107] and at least one of the above positive electrode layer and the above negative electrode layer is the electrode for a solid battery of the present disclosure.
[0108] The solid battery of the present disclosure may also include a positive electrode current collector on the side of the positive electrode layer opposite to the solid electrolyte layer side.
[0109] The solid battery of the present disclosure may include a negative electrode current collector on the side of the negative electrode layer opposite to the solid electrolyte layer side.
[0110] (Positive and negative electrode layers)
[0111] At least one of the positive electrode layer and the negative electrode layer included in the solid battery of the present disclosure is the solid battery electrode of the present disclosure.
[0112] The structure of the solid battery electrode other than the solid battery electrode of the present disclosure is not particularly limited, and a conventionally known structure may be adopted. For example, an electrode having a structure that does not contain a specific metal in the solid battery electrode of the present disclosure may be mentioned.
[0113] The solid battery electrode of the present disclosure is as described above, and therefore description thereof is omitted here.
[0114] The thickness of the positive electrode layer is not particularly limited, and may be, for example, 1 nm or more and 500 μm or less.
[0115] The thickness of the negative electrode layer is not particularly limited, and may be, for example, 1 nm or more and 500 μm or less.
[0116] (Solid electrolyte layer)
[0117] The solid electrolyte layer may contain a solid electrolyte. The solid electrolyte layer may be a single layer structure or a multilayer structure of more than two layers. As the solid electrolyte, a previously known substance that can be used for a solid electrolyte layer of a solid battery can be used, for example, a sulfide solid electrolyte can be cited.
[0118] The solid electrolyte layer may contain a binder. Examples of the binder include rubber-based binders such as styrene-butadiene rubber and fluoride-based binders such as polyvinylidene fluoride (PVDF).
[0119] The thickness of the solid electrolyte layer is not particularly limited, and may be, for example, 1 nm or more and 500 μm or less.
[0120] (Positive electrode collector)
[0121] As the positive electrode collector, a conventionally known positive electrode collector can be used. As the positive electrode collector, stainless steel, aluminum, nickel, iron, titanium, carbon, etc. can be cited, preferably aluminum alloy foil or aluminum foil. Aluminum alloy foil and aluminum foil can also be made using powder. The shape of the positive electrode collector is, for example, foil-like or mesh-like.
[0122] The thickness of the positive electrode current collector is not particularly limited, and may be, for example, 1 nm or more and 50 μm or less.
[0123] (Negative electrode current collector)
[0124] The negative electrode current collector may be any of the above-mentioned metal foils, preferably nickel foil or aluminum foil.
[0125] The thickness of the negative electrode current collector is not particularly limited, and may be, for example, 1 nm or more and 50 μm or less.
[0126] Figure 1 A schematic cross-sectional view showing one embodiment of a solid battery disclosed herein. Figure 1 As shown, a negative electrode layer A, a solid electrolyte layer B and a positive electrode layer C are stacked.
[0127] exist Figure 1 In the figure, reference numeral 101 denotes a negative electrode active material, reference numeral 103 denotes a positive electrode active material, reference numerals 105 and 107 denote conductive additives, reference numerals 109 and 111 denote binders, reference numeral 113 denotes a negative electrode collector, and reference numeral 115 denotes a positive electrode collector.
[0128] In addition, at least one of the negative electrode layer A and the positive electrode layer C contains a specific metal (not shown).
[0129] Solid batteries may also have a structure in which the stacked end faces (side faces) of the stacked structure of positive electrode / solid electrolyte layer / negative electrode are sealed with resin. The positive electrode collector and the negative electrode collector may also have a structure in which a buffer layer, an elastic layer or a PTC (Positive Temperature Coefficient) thermistor layer is arranged on the surface.
[0130] In addition, if Figure 1 As shown, the solid electrolyte layer may also have a two-layer structure.
[0131] An embodiment of the method for producing a solid battery of the present disclosure will be described below, but the present invention is not limited thereto.
[0132] First, a positive electrode mixture paste prepared by dissolving or dispersing a sulfide solid electrolyte, a specific metal, a positive electrode active material, a conductive aid, a binder, etc. in any solvent is applied to a positive electrode collector and dried to form a positive electrode layer, thereby manufacturing a positive electrode sheet having a positive electrode collector and a positive electrode layer.
[0133] Next, a negative electrode mixture paste prepared by dissolving or dispersing a sulfide solid electrolyte, a specific metal, a negative electrode active material, a conductive aid, a binder, etc. in any solvent is applied onto the negative electrode collector and dried to form a negative electrode layer, thereby producing a negative electrode sheet having a negative electrode collector and a negative electrode layer.
[0134] Next, a solid electrolyte layer paste prepared by dissolving or dispersing a solid electrolyte, a binder, etc. in an arbitrary solvent is applied to a metal foil such as aluminum foil or SUS foil and dried to form a solid electrolyte layer, thereby manufacturing a solid electrolyte sheet having a metal foil and a solid electrolyte layer.
[0135] Next, the negative electrode sheet and the solid electrolyte sheet are stacked, and the solid electrolyte layer is transferred to the surface of the negative electrode layer by pressing.
[0136] Next, a positive electrode sheet is stacked on the opposite side of the solid electrolyte layer to the negative electrode layer, and pressed to produce a solid battery.
[0137] The solid battery manufactured by the above method includes a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector in this order.
[0138] Examples of the solvent include water, N-methyl-2-pyrrolidone, butyl butyrate, tetralin, heptane, dibutyl ether, and diisobutyl ketone (DIBK).
[0139] [Example]
[0140] Hereinafter, the present disclosure will be described in more detail by way of examples, but the present disclosure is not limited to these examples.
[0141] <Example 1 to Example 7>
[0142] As the positive electrode active material, prepare LiNi 0.8 (CoAl) 0.2 O2. The positive electrode active material was surface treated with LTAF (Li-Ti-Al-F).
[0143] An ultrasonic homogenizer (UH-50 manufactured by SMT) is used to mix the positive electrode active material, conductive carbon, solid electrolyte (Li2S-P2S5-LiBr-LiI glass ceramics), binder (styrene-butadiene rubber (SBR)), solvent (tetralin) and copper to obtain a positive electrode mixture paste.
[0144] Furthermore, the content ratio (volume ratio) of the positive electrode active material and copper was set to the amount recorded in Table 1, and the amount of conductive carbon, solid electrolyte and binder was appropriately adjusted as the remainder to total the amount recorded in (other) in Table 1. When the sum of the contents of the positive electrode active material, conductive carbon, solid electrolyte, binder and copper was set to 100 parts by mass, the solvent was mixed in an amount of 25 parts by mass.
[0145] As the negative electrode active material, prepare Li4Ti5O 12 .
[0146] The negative electrode active material, conductive carbon, solid electrolyte, binder and solvent were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT) to obtain a negative electrode mixture paste. The solid electrolyte, binder and solvent used were the same as those used for the positive electrode mixture paste.
[0147] Furthermore, the content ratio (volume ratio) of the negative electrode active material was set to the amount described in Table 1, and the amounts of the conductive carbon, the solid electrolyte, and the binder were appropriately adjusted as the remainder to total the amount described in (other) in Table 1. When the sum of the contents of the negative electrode active material, the conductive carbon, the solid electrolyte, and the binder was set to 100 parts by mass, the solvent was mixed in an amount of 35 parts by mass.
[0148] 51 parts by mass of solvent, 3 parts by mass of a solution containing 5% by mass of a binder, and 46 parts by mass of LiI-LiBr-Li2S-P2S5 glass ceramics as a solid electrolyte were added to a polypropylene container and mixed for 30 seconds using an ultrasonic homogenizer (UH-50 manufactured by SMT). The binder and solvent used the same substances as the positive electrode mixture paste. Then, the container was vibrated for 3 minutes with an oscillator to obtain a solid electrolyte paste.
[0149] The positive electrode mixture paste was applied to the aluminum foil by a doctor blade method using an applicator, and then dried on a hot press at 100° C. for 30 minutes to obtain a positive electrode sheet having a positive electrode layer on the surface of the aluminum foil.
[0150] Similarly, the negative electrode mixture paste was applied onto an aluminum foil and dried to obtain a negative electrode sheet having a negative electrode layer.
[0151] Similarly, the solid electrolyte paste was applied to an aluminum foil and dried to obtain a solid electrolyte sheet having a solid electrolyte layer. Furthermore, the negative electrode unit weight was adjusted so that the charge capacity of the negative electrode was 1 times that of the positive electrode layer when the charge capacity was 200 mAh / g.
[0152] The negative electrode sheet and the solid electrolyte sheet are stacked, and the solid electrolyte layer is transferred to the negative electrode layer surface of the negative electrode sheet by pressing.
[0153] Next, the positive electrode sheet was stacked on the opposite side of the negative electrode layer of the solid electrolyte layer, and roll-pressed at 175° C. and 5 tons / cm to obtain a stacked body.
[0154] The laminated body has an aluminum foil, a positive electrode layer, a solid electrolyte layer, a negative electrode layer and an aluminum foil in this order.
[0155] The obtained stacked body was laminated and sealed, and restrained at 5 MPa to obtain an all-solid lithium ion secondary battery.
[0156] The all-solid lithium-ion secondary battery was left to stand for 7 days in an environment at a temperature of 80° C. This step is equivalent to the heat treatment of the solid battery.
[0157] <Example 8 to Example 16>
[0158] The positive electrode active material, conductive carbon, solid electrolyte, binder and solvent were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT) to obtain a positive electrode mixture paste. The same materials as in Example 1 were used for each material.
[0159] Furthermore, the content ratio (volume ratio) of the positive electrode active material was set to the amount recorded in Table 1, and the amounts of the conductive carbon, the solid electrolyte, and the binder were appropriately adjusted as the remainder to total the amount recorded in (other) in Table 1. When the sum of the contents of the positive electrode active material, the conductive carbon, the solid electrolyte, and the binder was set to 100 parts by mass, the solvent was mixed in an amount of 25 parts by mass.
[0160] The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT) to obtain a negative electrode mixture paste. The same materials as in Example 1 were used.
[0161] Furthermore, the content ratio (volume ratio) of the negative electrode active material and copper was set to the amount recorded in Table 1, and the amount of conductive carbon, solid electrolyte and binder was appropriately adjusted as the remainder to total the amount recorded in (other) in Table 1. When the sum of the contents of the negative electrode active material, conductive carbon, solid electrolyte, binder and copper was set to 100 parts by mass, the solvent was mixed in an amount of 35 parts by mass.
[0162] Except for using the positive electrode mixture paste and the negative electrode mixture paste, an all-solid lithium ion secondary battery was obtained in the same manner as in Example 1. Then, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, at a temperature of 80°C.
[0163] <Comparative Example 1>
[0164] The positive electrode active material, conductive carbon, solid electrolyte, binder and solvent were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT) to obtain a positive electrode mixture paste. The same materials as in Example 1 were used for each material.
[0165] Furthermore, the content ratio (volume ratio) of the positive electrode active material was set to the amount recorded in Table 1, and the amounts of the conductive carbon, the solid electrolyte, and the binder were appropriately adjusted as the remainder to total the amount recorded in (other) in Table 1. When the sum of the contents of the positive electrode active material, the conductive carbon, the solid electrolyte, and the binder was set to 100 parts by mass, the solvent was mixed in an amount of 25 parts by mass.
[0166] Except for using the above-mentioned positive electrode mixture paste, an all-solid lithium ion secondary battery was obtained in the same manner as in Example 1. Then, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, at a temperature of 80°C.
[0167] <Comparative Example 2>
[0168] The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT) to obtain a negative electrode mixture paste. The same materials as in Example 1 were used.
[0169] Furthermore, the content ratio (volume ratio) of the negative electrode active material and copper was set to the amount recorded in Table 1, and the amount of conductive carbon, solid electrolyte and binder was appropriately adjusted as the remainder to total the amount recorded in (other) in Table 1. When the sum of the contents of the negative electrode active material, conductive carbon, solid electrolyte, binder and copper was set to 100 parts by mass, the solvent was mixed in an amount of 35 parts by mass.
[0170] Except for using the above-mentioned negative electrode mixture paste, an all-solid lithium ion secondary battery was obtained in the same manner as in Example 8. Then, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, at a temperature of 80°C.
[0171] <<Resistance Evaluation>>
[0172] The obtained all-solid lithium ion secondary battery was placed in a thermostatic chamber set at 25° C. and connected to a charge and discharge device.
[0173] The battery was charged at a constant current equivalent to 0.1C, and constant voltage charging was performed after the battery voltage reached 2.7V. The constant voltage charging test was terminated when the current value reached the equivalent of 0.01C.
[0174] Next, the battery was discharged at a constant current of 0.1 C to 2.12 V corresponding to SOC 40, and constant voltage discharge was performed at 2.12 V. The constant voltage discharge was terminated when the current value reached 0.01 C.
[0175] Then, a constant current discharge was performed at 72C, and the DC resistance was calculated from the voltage after 0.1 seconds according to Ohm's law.
[0176] Table 1 shows the ratio of the resistance values of the Examples and Comparative Examples, when the resistance value of the all-solid lithium ion secondary battery of Comparative Example 1 is set to 100%.
[0177] Table 1
[0178]
[0179] From the results in Table 1, it can be seen that the solid battery of the embodiment in which the content of the metal (copper) relative to the total volume of the solid battery electrode is 5 volume ppm or more has a lower resistance after heat treatment and a lower resistance increase than the solid battery of Comparative Example 1 which does not contain the metal. In addition, it can be seen that the solid battery of the embodiment in which the content of the metal (copper) relative to the total volume of the solid battery electrode is set to less than 10,000 volume ppm has a lower resistance after heat treatment and a lower resistance increase than the solid battery of Comparative Example 2 in which the content of the metal (copper) is an amount exceeding this range.
[0180] The details of the test to confirm that copper is a metal that reacts with a sulfide solid electrolyte to exhibit electron conductivity will be described later.
[0181] <Examples 17 to 20 and Comparative Examples 3 to 4>
[0182] The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent and silver were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT) to obtain a negative electrode mixture paste. The same materials as in Example 1 were used for each material.
[0183] Furthermore, the content ratio (volume ratio) of the negative electrode active material and silver was set to the amount recorded in Table 2, and the amount of conductive carbon, solid electrolyte and binder was appropriately adjusted as the remainder to total the amount recorded in (other) in Table 2. When the sum of the contents of the negative electrode active material, conductive carbon, solid electrolyte, binder and silver was set to 100 parts by mass, the solvent was mixed in an amount of 35 parts by mass.
[0184] Except for using the above-mentioned negative electrode mixture paste, an all-solid lithium ion secondary battery was obtained in the same manner as in Example 8. Then, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, at a temperature of 80°C.
[0185] <<Resistance Evaluation>>
[0186] The resistance of the obtained all-solid lithium ion secondary battery was evaluated in the same manner as in Example 1.
[0187] Table 2 shows the ratio of the resistance values of each Example and each Comparative Example, when the resistance value of the all-solid lithium ion secondary battery of Comparative Example 1 is set to 100%.
[0188] Table 2
[0189]
[0190] From the results in Table 2, it can be seen that the solid battery of the embodiment in which the content of metal (silver) relative to the total volume of the solid battery electrode is 5 volume ppm or more and less than 10,000 volume ppm has lower resistance after heat treatment and reduced resistance increase compared to the solid battery of the comparison example containing more than 10,000 volume ppm.
[0191] The details of the test to confirm that silver is a metal that reacts with the sulfide solid electrolyte to exhibit electron conductivity will be described later.
[0192] <Comparative Examples 5 to 8>
[0193] The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent and stainless steel SUS316 were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT) to obtain a negative electrode mixture paste. The same materials as in Example 1 were used.
[0194] Furthermore, the content ratio (volume ratio) of the negative electrode active material and stainless steel SUS316 was set to the amount described in Table 3, and the amount of conductive carbon, solid electrolyte and binder was appropriately adjusted as the remainder to total the amount described in (other) in Table 3. When the sum of the contents of the negative electrode active material, conductive carbon, solid electrolyte, binder and stainless steel SUS316 was set to 100 parts by mass, the solvent was mixed in an amount of 35 parts by mass.
[0195] Except for using the above-mentioned negative electrode mixture paste, an all-solid lithium ion secondary battery was obtained in the same manner as in Example 8. Then, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, at a temperature of 80°C.
[0196] <<Resistance Evaluation>>
[0197] The resistance of the obtained all-solid lithium ion secondary battery was evaluated in the same manner as in Example 1.
[0198] Table 3 shows the ratio of the resistance values of the respective Comparative Examples, when the resistance value of the all-solid lithium ion secondary battery of Comparative Example 1 is set to 100%.
[0199] Table 3
[0200]
[0201] From the results in Table 3, it is understood that the solid battery of the comparative example in which the solid battery electrode contains stainless steel SUS316 has high resistance after heat treatment, and the resistance increase is not reduced.
[0202] The details of the test to confirm that stainless steel SUS316 is not a metal that reacts with the sulfide solid electrolyte to exhibit electron conductivity will be described later.
[0203] <Comparative Example 9 to Comparative Example 10>
[0204] The positive electrode active material, conductive carbon, solid electrolyte, binder, solvent and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT) to obtain a positive electrode mixture paste. The same materials as in Example 1 were used for each material.
[0205] Furthermore, the content ratio (volume ratio) of the positive electrode active material and copper was set to the amount described in Table 4, and the amount of conductive carbon, solid electrolyte and binder was appropriately adjusted as the remainder to total the amount described in (other) of Table 4. When the sum of the contents of the positive electrode active material, conductive carbon, solid electrolyte, binder and copper was set to 100 parts by mass, the solvent was mixed in an amount of 25 parts by mass.
[0206] Except for using the above-mentioned positive electrode mixture paste, an all-solid lithium ion secondary battery was obtained in the same manner as in Example 1. Then, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, at a temperature of 80°C.
[0207] <Comparative Example 11>
[0208] The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT) to obtain a negative electrode mixture paste. The same materials as in Example 1 were used.
[0209] Furthermore, the content ratio (volume ratio) of the negative electrode active material and copper was set to the amount described in Table 4, and the amount of the conductive carbon, the solid electrolyte and the binder was appropriately adjusted as the remainder to total the amount described in (other) in Table 4. When the sum of the contents of the negative electrode active material, the conductive carbon, the solid electrolyte, the binder and the copper was set to 100 parts by mass, the solvent was mixed in an amount of 35 parts by mass.
[0210] Except for using the above-mentioned negative electrode mixture paste, an all-solid lithium ion secondary battery was obtained in the same manner as in Example 1. Then, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, at a temperature of 80°C.
[0211] <<Short circuit suppression evaluation (self-discharge evaluation)>>
[0212] The obtained all-solid lithium ion secondary battery was placed in a thermostatic chamber set at 25° C. and connected to a charge and discharge device.
[0213] Constant voltage charging was performed at 2.515 V. Constant voltage charging was terminated when the current value decayed to 0.01 C. Then, the battery voltage was measured at open circuit voltage for 72 hours. The voltage drop over 24 hours between 48 hours and 72 hours was calculated as the self-discharge amount.
[0214] The above-mentioned self-discharge amount was measured for Examples 3 to 7, Examples 11 to 16, Comparative Examples 1 to 2, and Comparative Examples 9 to 11, and the results are summarized in Table 4.
[0215] Table 4
[0216]
[0217] From the results in Table 4, it can be seen that the solid batteries of Examples 3 to 6 and Examples 11 to 15, in which the content of metal (copper) relative to the total volume of the solid battery electrode is less than 4000 volume ppm, have smaller self-discharge and improved short-circuit suppression than the solid batteries of Examples 7, 16 and the comparative example, in which the content exceeds 4000 volume ppm.
[0218] <Examples 21 to 25>
[0219] The positive electrode active material, conductive carbon, solid electrolyte, binder, solvent and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT) to obtain a positive electrode mixture paste. The same materials as in Example 1 were used for each material.
[0220] Furthermore, the content ratio (volume ratio) of the positive electrode active material and copper was set to the amount recorded in Table 5, and the amount of conductive carbon, solid electrolyte and binder was appropriately adjusted as the remainder to total the amount recorded in (other) in Table 5. When the sum of the contents of the positive electrode active material, conductive carbon, solid electrolyte, binder and copper was set to 100 parts by mass, the solvent was mixed in an amount of 25 parts by mass.
[0221] The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT) to obtain a negative electrode mixture paste. The same materials as in Example 1 were used.
[0222] Furthermore, the content ratio (volume ratio) of the negative electrode active material and copper was set to the amount described in Table 5, and the amount of conductive carbon, solid electrolyte and binder was appropriately adjusted as the remainder to total the amount described in (other) of Table 5. When the sum of the contents of the negative electrode active material, conductive carbon, solid electrolyte, binder and copper was set to 100 parts by mass, the solvent was mixed in an amount of 35 parts by mass.
[0223] Except for using the positive electrode mixture paste and the negative electrode mixture paste, an all-solid lithium ion secondary battery was obtained in the same manner as in Example 1. Then, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, at a temperature of 80°C.
[0224] <<Resistance Evaluation>>
[0225] The resistance of the obtained all-solid lithium ion secondary battery was evaluated in the same manner as in Example 1.
[0226] Table 5 shows the ratio of the resistance values of the respective Examples when the resistance value of the all-solid lithium ion secondary battery of Comparative Example 1 is set to 100%.
[0227] <<Short circuit suppression evaluation (self-discharge evaluation)>>
[0228] The short-circuit suppressability of the obtained all-solid lithium ion secondary battery was evaluated in the same manner as in Example 1. Table 5 shows the results of the self-discharge amount.
[0229]
[0230] <<Verification of whether metal is a specific metal>>
[0231] For "copper, silver, stainless steel SUS316" used in the above examples, and nickel, aluminum, gold, iron, platinum, and zinc not used in the above examples, it was confirmed whether they were metals (specific metals) that reacted with the sulfide solid electrolyte to exhibit electron conductivity according to the above verification method. The results of the measured increase rate of electron conductivity before and after heat treatment are shown in Table 6.
[0232] Table 6
[0233]
Claims
1. A solid battery electrode comprising: Sulfide solid electrolytes, and a metal that reacts with the sulfide solid electrolyte to exhibit electronic conductivity, The content of the metal relative to the total volume of the solid battery electrode is 5 volume ppm or more and less than 10,000 volume ppm.
2. The solid battery electrode according to claim 1, The metal is at least one metal selected from the group consisting of copper, silver, nickel, iron, tin, aluminum, titanium, chromium, zinc, gold, magnesium, antimony, zirconium, molybdenum and alloys thereof.
3. The solid battery electrode according to claim 2, The metal is at least one of copper and silver.
4. The solid battery electrode according to claim 1, The content of the metal relative to the total volume of the solid battery electrode is 50 volume ppm or more.
5. The solid battery electrode according to claim 1, The content of the metal relative to the total volume of the solid battery electrode is 5,000 ppm by volume or less.
6. The solid battery electrode according to claim 1, The sulfide solid electrolyte contains phosphorus atoms.
7. A solid battery comprising a positive electrode layer, a solid electrolyte layer and a negative electrode layer, At least one of the positive electrode layer and the negative electrode layer is the solid battery electrode according to any one of claims 1 to 6.
